2019
DOI: 10.3390/ijms20092077
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin Levels in Preterm and Term Infants and Their Mothers

Abstract: The prevention of perinatal brain damage following preterm birth remains a public health priority. Melatonin has been shown to be a promising neuroprotectant in neonatal preclinical models of brain damage, but few studies have investigated melatonin secretion in newborns. We hypothesized that melatonin circulating levels would be lower in preterm compared to term infants. We conducted a prospective, longitudinal, multicenter study to assess melatonin, and 6-sulfatoxy-melatonin (aMT6s) concentrations, measured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
52
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(58 citation statements)
references
References 28 publications
4
52
0
2
Order By: Relevance
“…An interesting collaborative study from several clinical and academic French institutions provides here evidence that the melatonin circulating levels at day of birth are much lower-below detection-in 78% of infants born before 34 GW [18]. This was also confirmed with urine aMT6s concentrations.…”
supporting
confidence: 54%
“…An interesting collaborative study from several clinical and academic French institutions provides here evidence that the melatonin circulating levels at day of birth are much lower-below detection-in 78% of infants born before 34 GW [18]. This was also confirmed with urine aMT6s concentrations.…”
supporting
confidence: 54%
“…Three-to-five months may pass after birth before a full-term newborn produces melatonin, experiencing a transient deficiency in melatonin levels [ 39 ]. Preterm infant research has given unclear findings: reduced urine aMT6s levels have been described at birth [ 40 ], but other studies have reported decreased 6-sulfatoxy-melatonin urine concentrations for 13 weeks after birth in preterm infants when compared to term infants [ 41 ].…”
Section: Melatoninmentioning
confidence: 99%
“…Some stressful conditions not ruled out in other studies may modify the results. 20 Indeed, the characteristics of the population studied in this research are more homogeneous, and fewer adverse inflammatory or oxidative effects were expected.…”
Section: Discussionmentioning
confidence: 92%